E-Service Quality at Livin' by Mandiri Users: The Mediating Role of E-Customer Satifaction on E-Customer Loyalty - Fitriyah Nurjanah; Ela Anatasya Hutabarat; Lis Tatin Hernidatiatin (Universitas KH. Abdul Chalim Mojokerto, 2025)
Currently, the banking world is competing fiercely to provide the best service to customers, especially in the realm of Mobile Banking. The purpose of this study was to determine the effect of e-service quality on e-customer loyalty through e-customer satisfaction as a mediating variable in m-banking users, especially livin' by Mandiri users. This study uses quantitative research methods with sampling techniques using a purposive sampling approach; the samples taken in this research were 400 respondents of livin’ by mandiri users. The data obtained will be processed through Microsoft Excel, and then continued data analysis using Smart-PLS.The results of this study show that e-service quality affects Livin'by Mandiri user e-customer satisfaction, e-service quality affects Livin' by Mandiri user e-customer loyalty, e-customer satisfaction affects Livin'by Mandiri user e-customer loyalty, and e-customer satisfaction mediates the relationship between e-service qualty and the e-customer loyalty of Livin'by Mandiri users.